THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND ELDERLY ACTIVENESS IN JOINING ELDERLY POSYANDU ACTIVITIES - Heri Triwibowo; Heni Frilasari; Fajar Ashari (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Along with the increasing elderly population, the government has formulated various health service policies aimed at the elderly, one of which is the elderly Posyandu. This health service is intended to improve the health status of the elderly. The purpose of this study was to determine the relationship between family support and the activeness of the elderly in participating in elderly Posyandu activities in Alley 7, Sawahan Village, Mojosari District. The research design used was an analytic correlation with a cross-sectional study approach. The population is all elderly people who are registered at the gang 7 elderly Posyandu as many as 34 people and are taken using a non-probability sampling technique, namely the saturated sampling technique. The independent variable is family support and the dependent variable is the activeness of the elderly in participating in elderly Posyandu activities. Data collection was carried out by distributing questionnaires and KMS observation sheets, after the data was collected, the data was processed using the chi-square test with the help of SPSS 16 at the error level (α) = 0.05 value (ϼ) value = 0.012 <0.05 then H1 was accepted and H0 is rejected, which means that there is a relationship between family support and the activeness of the elderly in participating in elderly Posyandu activities in alley 7, Sawahan Village, Mojosari District. The existence of family support for the elderly causes peace of mind and happiness in the elderly. Family support will affect the activity of the elderly because the role of the family is very important in encouraging and motivating the interest of the elderly to be active in Posyandu.